New or rare Madagascar tiger beetles—21. Physodeutera (Microlepidia) propripenis sp. nov., Ph. (M.) marginemaculata (W. Horn) and Ph. (M.) peyrierasi Rivalier (Coleoptera: Cicindelidae) - Moravec, Jiří; Brzoska, David; Vybíral, Jan (Zootaxa, 2021)
A new species of the Madagascan endemic genus Physodeutera Lacordaire, 1842 is described from northern Madagascar as Physodeutera (Microlepidia) propripenis sp. nov. The new species is compared to similar Physodeutera (Microlepidia) marginemaculata (W. Horn, 1934) and Physodeutera (Microlepidia) peyrierasi Rivalier, 1967. Apart from a detailed description of the new species, illustrations in colour photographs of its habitus, diagnostic characters and habitat are introduced. Differential diagnoses of the two similar species, as well as illustrations of their habitus and distinguishing characters in colour photographs are presented with references to their redescriptions and illustrations based on type and other relevant specimens in the monograph of the genus (Moravec 2002a). A revised key to the subgenus Microlepidia Rivalier, 1967 is presented in order to supplement the key previously published in the monograph. Essential maps of the distribution of the three species are also given.